Beyond Shari‘ah compliance: achieving Maqasid Al-Shari‘ah through Social Impact Bonds (SIB) and Sustainable & Responsible Investment (SRI) Sukuk - Syed Azman, Syed Marwan Mujahid; Haneef, Mohamed Aslam; Engku Ali, Engku Rabiah Adawiah; Ismail, Suhaiza (Kolej Profesional Baitulmal Kuala Lumpur (KPBKL), 2021)
This paper looks into the underlying principles of Social Impact Bond (SIB) and Sustainable and Responsible Investment (SRI) sukuk as compared to the values embodied within maqasid al-Shari’ah and maslahah. The paper attempts to delineate the elements embedded within these financial tools from an Islamic perspective through a critical review of literature related to SIB, SRI sukuk, maqasid al-Shari’ah and maslahah. The paper explicates that SIB and SRI sukuk are financial instruments that epitomises the ethical and moral framework of the Shari’ah as their underlying principles are congruent with the concepts within maqasid al-Shari’ah and maslahah. Thus, the SIB and SRI sukuk models should be given more attention by Islamic banks and Islamic financial institutions whose philosophical foundation is built upon the principles of maqasid al-Shari’ah and maslahah.